A critique of longtermism and human rights of a non-existent future based on dystopian fiction - FÉLIX MOREIRA JÚNIOR, Ronaldo; CAMATTA MOREIRA, Nelson (Utopía y Praxis Latinoamericana, 2025)
This article examines the concept of longtermism and its impact on the provision of human rights in the present, analyzing the tension between concerns for future generations and the realization of current rights. Through a comparison with dystopian fiction, it shows how this philosophy can legitimize inequalities and challenge the fight for human rights. The qualitative methodology and dialectical method allow for a deep understanding of these phenomena. The work, based on authors like David Sanchez Rubio, also discusses the negative influence of longtermism, promoted by influential figures, on the provision of rights in the present.